Women at the dawn of history - Lassen, Agnete W., 1979-; Wagensonner, Klaus (Yale Babylonian Collection, Peabody Museum of Natural History, Yale University, 2020)
In the patriarchal world of ancient Mesopotamia, women were often represented in their relation to men - as mothers, daughters, or wives - giving the impression that a woman's place was in the home. But, as we explore in this volume, they were also authors and scholars, astute business-women, sources of expressions of eroticism, priestesses with access to major gods and goddesses, and regents who exercised power on behalf of kingdoms, states, and empires.